Challenges of participatory-deliberative governance in the era of social media digitalisation - Czepczyński, Mariusz (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2016)
Question of public involvement in urban development processes grows to be among the major contemporary issues of new urban governance. Local powers, traditionally based on the elected bodies (the council and the mayor) is recently being challenged by growing, often unstructured and informal urban movements. New powers have been renegotiating supremacy relations, often using social media and digital tools. The same time digital tools are used by municipalities to expand public participation. Direct participation in urban management evolve to be a basic civic right, but it is seldom correlated with responsibilities and consequences of common, especially digital, decisions. New apps and programs create many opportunities for public participation, but social media often lack broader consideration, compromise and conciliation. Simplistic digital participation can be easily fuelled by internet ignorance, expertise relativism or ‘balanced routine’.
Keywords: governance; democracy; participation; deliberation; hybridisation; social media; planning; slacktivism; agnotology